Hochst Oral History Transcript - Hochst, Hartmut (My University, 2009)
Transcript of an oral history with Hartmut Hochst, scientific director, of the Synchrotron Radiation Center. Conducted by Eric Verbeten.
Keywords: Synchrotron, Hochst